Wincenty Skrzetuski o sukcesji tronu i porządku obrad sejmu - Organiściak , Wojciech (Czasopismo Prawno-Historyczne, 2009)
Wincenty Skrzetuski's political views place him among the followers of the designers of the reform of the 18th century Republic of Poland. In his work on The Political Right of the Polish Nation, Skrzetuski described the principles according to which the Polish Seym of those times functioned, and, more importantly, depicted the liberum veto rule which he considered to be one of the most disastrous mechanisms allowing an abuse of civil rights. He also proposed procedures that would facilitate a better and more efficient conduct of parliamentary sessions and enhance discipline among its participants. Skrzetuski's views on the succession to the throne expressed in his work on Speeches on major political matters are also noteworthy. His criticism of Royal Election constituted an important element in the 18th century dispute between the supporters of the old order and the propagators of the reforms. Skrzetuski was among those who were first to advocate the necessity of building a strong modern state. In his works such a Speeches or The Political Right he often warned that delaying reforms, e.g. such as introduction of the succession to the throne, or maintaining the liberum veto principle, would lead to a decline and ultimate fall of the Republic.